البرادي حياته و آثاره - العدالي, سالم (مجلة الهداية, 1983)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-

‏أعلام من الماضي الشيخ أبو الفاضل أبو القاسم بن إبراهيم البرادي - الباروني, سعيد بن يوسف (الجزيرة, 1994)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Biographies -- Djerba

الدمري ق5هـ/11م - عبد الوهاب, حسن حسني (كتاب العمر في المصنفات والمؤلفين التونسيين, 1990)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Biographies

رسالة الحقائق تأليف: أبي الفضل البرادي القرن الثامن الهجري. تحقيق وتقديم - العدالي, سالم (الكلية الزيتونية للشريعة وأصول الدين, 1982)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-

دراسة فى تاريخ الإباضية وعقيدتها: مع رسالة فى كتب الإباضية - البرادي, أبو القاسم بن إبراهيم (دار الفضيلة, 1994)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-

Il califfo ʿAbd al-Malik b. Marwān e gli Ibāḍiti - Rubinacci, Roberto (Annali dell'Istituto Universitario Orientale di Napoli, 1953)
Pp. 106-121: translation of a letter by ʿAbdl. b. Ibāḍ (2nd Ṭabaqa, 50-100 A.H.) addressed to ʿAbd al-Malik b. Marwān, on the administration of Abū Bakr, ʿUmar and ʿUthmān; from Barrādī: Kitāb al-Jawāhir, Cairo 1302/1884-5, 156-167.
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Orientalisme -- Italie

Il "Kitāb al-Jawāhir" di al-Barrādī - Rubinacci, Roberto (Annali dell'Istituto Universitario Orientale di Napoli, 1952)
A detailed study of Barrādī’s book and a conclusion of its position among the sources for the study of the history of early Islam and the origins of the Ibāḍiyya. Rubinacci mentions in detail Barrādī’s sources and makes i.a. a comparison with Darjīnī’s Ṭabaqāt al-Mashāyikh (103-104).
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Orientalisme -- Italie

Notizia di alcuni manoscritti ibāḍiti esistenti presso l’Istituto Universitario Orientale di Napoli - Rubinacci, Roberto (Annali dell'Istituto Universitario Orientale di Napoli, 1949)
The following MSS are mentioned: Qawāʿid by Jayṭālī with glosse by Abū Sitta al-Qaṣbī; K. al-Siyar of Shammākhī; K. al-Jawāhir by Barrādī; Mukhtaṣar K. al-Khiṣāl by Abū Isḥāq Ibr. [b. Qays al-Ḥadramī]; K. al-Waḍʿ fī ‘l-Furūʿ by Jannāwunī; Qanāṭir al-Khayrāt by Jayṭālī; Mukhtaṣar by Muḥ. b. Mulūka al-Tūnisī of the same’s commentary on Durrat al-Bayḍā’ by ʿAbd al-Raḥmān al-Akhḍarī (see GAL S I, 778; S II, 706).
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Jayṭālī, Ismāʿīl b. Mūsà (13..-1350)

Un antico documento ibāḍita sul Corano creato. La Risāla dell’Imam Rustemide Muḥammad Abū ‘l-Yaqẓān - Cremonesi, Vanna (Studi Magrebini, 1966)
A study with a translation of the Risāla of the Rustemid Imam Abū ‘l-Yaqẓān (Muḥ.) b. Aflaḥ b. ʿAbd al-Wahhāb in Barrādī’s K. al-Jawāhir, on the creation of the Koran.
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Orientalisme -- Italie

Un antico documento di vita cenobitica musulmana. La regola della ḥalqa dello shaykh Abū ʿAbdl. Muḥ. b. Bakr - Rubinacci, Roberto (Annali dell'Istituto Universitario Orientale di Napoli, 1960)
A study, with a translation, of Abū ʿAbdl. Muḥ. b. Bakr’s rules of the Ḥalqa, from Darjīnī’s K. Ṭabaqāt al-Mashāyikh (MS in the library of the University of Cracow, f. 47r line 15-f. 51v). A comparison is made with the same text in Barrādī’s K. al-Jawāhir al-Muntaqāt (Cairo 1302/1884-5, 207-218).
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Orientalisme -- Italie

Traduzione di passi riguardanti il conflitto ʿAlī-Muʿāwiya e la secessione khārigita dal Kitāb al-Jawāhir di al-Barrādī - Veccia Vaglieri, Laura (Annali dell'Istituto Universitario Orientale di Napoli, 1953)
Translations with comments and annotations from: Barrādī: K. al-Jawāhir (lith., Cairo 1302/1884-5, 111-147) (1-73); Shammākhī: K. al-Siyar (Cairo 1301, 45-56) (74-87); Naṣr b. Muzāḥim al-Minqarī: Waqʿat Ṣiffīn (88-92); index of names and Arabic terms in Veccia Vaglieri 1952 and in this article (92-98).
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Fitnah

Il conflitto ʿAlī-Muʿāwiya e la secessione khārigita riesaminati alla luce di fonte ibāḍite - Veccia Vaglieri, Laura (Annali dell'Istituto Universitario Orientale di Napoli, 1952)
the ʿAlī - Muʿāwiya conflict is a historical moment which is interesting not only owing to the very serious consequences it brought in the Islamic world, but because it gives rise to a lot of problems still unsolved or whose solution is not satisfactory. The islamists had till now for the study of the Caliphate of ʿAlī availed themselves only of philo-alid or philo-umayyad sources. The author has observed, in the course of her reading Ibāḍī texts, that two of them, the Jawāhir of al-Barrādī and the Siyar of al-Shammākhī, have handed down to us on this period of history very ancient Khārijite or philo-khārijite traditions taken from K. al-Nahrawān which was probably composed during the first half of the 2nd century A.H. The above said traditions have been of great importance to the author for two reasons, i.e.: they allowed her to fix the point of view of the Khārijites, a vague point till now; and have supplied her with the key to enable her to understand many passages of other sources (Ṭabarī, Balādhurī, Dīnawarī, Yaʿqūbī, Masʿūdī, etc. already studied by the islamists, and the Waqʿat Ṣiffīn of Naṣr b. Muzāḥim almost not utilized till now, while it supplies with information of the greatest importance).
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Fitnah

البرادي حياته و آثاره وآرأه العقدية - العدالي, سالم (جامعة تونس, 1982)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-

أبو الفاضل أبو القاسم بن إبراهيم البرادي - الباروني, سعيد بن يوسف (اعلام من جزيرة جربة, 1996)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Biographies -- Djerba

Bibliothèques et manuscrits Abadites - Schacht, Joseph (Revue Africaine, 1956)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Bibliothèques -- Djerba; Bibliothèques -- Mzab; Manuscrits -- Djerba; Manuscrits -- Mzab

Barrādī al- - Rubinacci, Roberto (Encyclopédie de l'Islam, 1960)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-

Les Ibadites du Sud tunisien du 3e/IXe au 6e/XIIe siècles - Ben Yahyaten, Sassi (Université Paris 1, 1983)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-

Aperçu sur l'histoire religieuse des Ibādites du Mzab en Algérie ("La Sīrat al Halga" d'Abū 'Abd Allāh Muhammad ben Bakr al Nafūsi (IV=Xe siècle) dans la version extraite du "Kitāb al Gawāhir al muntagāt" d'Abū al Fadl Abū al Qāsim al Barrédī (VIII=XIV siècle) - Grossmann, Claude (Université Paris 4, 1976)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-